Leaf Light Reflectance for Evaluating Red Oak Lettuce Cultivated under Low Light Intensity - Thussagunpanit, Jutiporn; Nakklay, Panisra; Sukkrom, Kanokwan; Sonjaroon, Weerasin (Science Essence Journal, 2020)
บทคัดย่อ แสงเป็นปัจจัยสำคัญที่มีผลต่อการเจริญเติบโตของผักสลัดบริโภคใบ โดยผักที่ปลูกภายใต้สภาพ ความเข้มแสงต่ำจะมีผลผลิตลดลง การตรวจสอบการเปลี่ยนแปลงทางสรีรวิทยาของผักเมื่อได้รับความเข้มแสงไม่เพียงพอจึงเป็นข้อมูลที่นำไปใช้ในการจัดการระบบปลูก ในการศึกษาครั้งนี้ใช้คุณสมบัติการสะท้อนของใบเพื่อเปรียบเทียบการเปลี่ยนแปลงทางสรีรวิทยาของผักกาดหอมเรดโอ๊คที่ปลูกในระบบไฮโดรพอนิกส์ในสภาพความเข้มแสงปกติและในสภาพความเข้มแสงต่ำกว่าปกติ ผลการทดลองพบว่าผักกาดหอมเรดโอ๊คที่ปลูกในสภาพความเข้มแสงต่ำกว่าปกติมีความกว้างทรงพุ่มและน้ำหนักสดลดลง นอกจากนี้ความเข้มแสงต่ำยังส่งผลให้ปริมาณแอนโธไซยานินในใบของผักกาดหอมเรดโอ๊คลดลง เมื่อตรวจวัดค่าการสะท้อนแสงและนำมาคำนวณดัชนีสเปกตรัมพบว่า ดัชนี Green Normalized Difference Vegetable Index (GNDVI) และดัชนี Anthocyanin Reflectance Index (ARI1 และ ARI2) ของใบผักกาดหอมเรดโอ๊คที่ปลูกในสภาพความเข้มแสงปกติมีค่าสูงกว่าผักกาดหอมเรดโอ๊คที่ปลูกในสภาพความเข้มแสงต่ำกว่าปกติ และดัชนีสเปกตรัมทั้งสามนี้ยังมีสหสัมพันธ์กับปริมาณแอนโธไซยานินในใบ ความแตกต่างของค่าการสะท้อนแสงในใบผักกาดหอมเรดโอ๊คที่ปลูกในสองสภาพความเข้มแสงนี้สามารถนำไปใช้ตรวจสอบสุขภาพพืชเพื่อใช้จัดการความเข้มแสงในโรงเรือนต่อไป ABSTRACT Light is an important factor for the growth and development of leafy salad vegetables. Vegetables cultivated under low light intensity will produce a low yield. The monitoring of physiological changes in vegetables grown under inadequate light intensity is the information for planting system management. In this study, leaf light reflectance was investigated in order to compare the physiological changes of Red Oak lettuce that were hydroponically grown under normal light intensity and under lower light intensity than usual. The result showed that Red Oak lettuce grown under lower light intensity than usual had small canopy width and low fresh weight. Moreover, low light intensity could reduce the anthocyanin production in leaves of Red Oak lettuce. The leaf light reflectance was measured and then calculated to various spectral indices. Red Oak lettuce grown under normal light intensity exhibited higher Normalized Difference Vegetable Index (GNDVI) and Anthocyanin Reflectance Index (ARI1 and ARI2) which are kinds of spectral index than that of Red Oak lettuce grown under lower light intensity than usual. Moreover, those three spectral indices had a correlation with the anthocyanin content in leaves. Differences of leaf light reflectance in Red Oak lettuce cultivated under two conditions of light intensity could be applied to monitor plant health for management of the light intensity in a plant nursery in the future.